Building Resilience in Education Systems with Open and Flexible learning: Construindo resiliência em sistemas educacionais com aprendizagem aberta e flexível (Revista Cocar, 2024)
In a recent publication “The Handover: How we gave control of our lives to corporations, states and AI, David Runciman suggests there are a few things that pose an existential threat to the human species (Runciman, 2023, p. 256). The question is what are we doing about it―as a society? In this paper we direct our attention to one region of the globe—the South West Pacific region which is home to small island states at various levels of development. Many of these island states face serious threats from the impacts of climate change. As a result, Pacific Islanders continue to leave the region for further education and employment. In order to retain its intellectual capital, a different mindset and value propositions are required for these island nations in relation to how they see educational provision in their countries. This means seeing educational provision with a new set of lenses that requires a fundamental re-engineering of how education is funded and provided. In this paper we explore the opportunities for that kind of transformationKey-words: Flexible learning; Resilience in Education; Systems with Open.  ResumoEm uma publicação recente “The Handover: How we gave control of our lives to corporations, states and AI”, David Runciman sugere que há algumas coisas que representam uma ameaça existencial para a espécie humana (Runciman, 2023, p. 256). A questão é o que estamos fazendo sobre isso — como uma sociedade? Neste artigo, direcionamos nossa atenção para uma região do globo — a região do Sudoeste do Pacífico, que abriga pequenos estados insulares em vários níveis de desenvolvimento. Muitos desses estados insulares enfrentam sérias ameaças dos impactos das mudanças climáticas. Como resultado, os habitantes das ilhas do Pacífico continuam a deixar a região para obter mais educação e emprego. Para reter seu capital intelectual, uma mentalidade e propostas de valor diferentes são necessárias para essas nações insulares em relação a como elas veem a oferta educacional em seus países. Isso significa ver a oferta educacional com um novo conjunto de lentes que requer uma reengenharia fundamental de como a educação é financiada e fornecida. Neste artigo, exploramos as oportunidades para esse tipo de transformação.Palavras-chave: Aprendizagem flexível; Resiliência na Educação; Sistemas abertos.
Keywords: Flexible learning; Resilience in Education; Systems with Open.